Financial and economic dissonances of the consequences of the war in Ukraine - Chkan, Iryna; Чкан, Ірина Олександрівна (Chicago, USA, 2023)
The article presents the financial and economic dissonances of the consequences of the war for Ukraine, which consist in the fact that despite the acceleration of inflation, the increase in the value of money, the deterioration of credit quality and the reduction of incentives for long-term storage of money in government accounts, the stability of the economy is maintained. Radical changes in the structure of the national budget due to a significant increase in defense spending and the planned deficit affected the financial system, but the correct application of macroeconomic tools quickly overcame the negative reaction.
Keywords: economy; financial system; budget; inflation; exchange rate